2017
DOI: 10.1016/j.jtusci.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial activities of ethanol extracts ofEuphorbia hirtawhole plant andVernonia amygdalinaleaves inPlasmodium berghei-infected mice

Abstract: The African continent is rich in both flora and fauna resources, which have been extensively used locally in the treatment or cure of a wide variety of ailments. Enquiries into traditional folklore revealed that Euphorbia hirta and Vernonia amygdalina possess antiplasmodial properties among others for the treatment of febrile conditions. We therefore investigated the phytochemistry, antimalarial potencies, hepatic toxicities and renal toxicities of the crude ethanol extract of the whole plant of Euphorbia hirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
3
19
0
1
Order By: Relevance
“…The highest suppression was recorded in the methanol extract treated mice (83.36% at the oral dose of 600 mg/kg). Previous studies have demonstrated the presence of secondary metabolites such as alkaloids, steroids, saponins, flavonoides, anthraquinones, terpenoids, sterols, diterpenoid, glycosides, tannins and sesquiterpene lactones in Vernonia species [7, 19]. The parasitaemia inhibition could be attributed to the presence of these metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The highest suppression was recorded in the methanol extract treated mice (83.36% at the oral dose of 600 mg/kg). Previous studies have demonstrated the presence of secondary metabolites such as alkaloids, steroids, saponins, flavonoides, anthraquinones, terpenoids, sterols, diterpenoid, glycosides, tannins and sesquiterpene lactones in Vernonia species [7, 19]. The parasitaemia inhibition could be attributed to the presence of these metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium berghei , a rodent malaria parasite maintained at the parasite bank of CBRD, KEMRI, was used. The assay protocol was based on Peter's 4-day suppression test [ 17 ]. The parasite strain was maintained by a serial passage of blood from an infected mouse to a naïve mouse.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental mice were randomly divided into three groups of five consisting of treatment and the controls (positive and negative) [ 17 ]. Each mouse was infected interperitoneally with 0.2 ml inoculum (1% parasitemia).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the anti-inflammatory, digestive, neuroprotective, hepatoprotective and nephroprotective drugs derived from natural origin have been reported to have antioxidant/radical scavenging mechanism as part of their activity ( Oladele et al., 2020b , c ; Oyewole et al., 2017 ). The ingestion of natural antioxidants has been associated with the reduced risk of cancer, cardiovascular disease, diabetes and other diseases associated with ageing ( Ajayi et al., 2017 ). Hence, interest has been increased for finding antioxidants of plant source, which are safe and suitable for use in food and/or medicine.…”
Section: Medicinal Plants With Pharmacological and Biological Action mentioning
confidence: 99%